Treatment of Burn and Surgical Wounds With Recombinant Human Tropoelastin Produces New Elastin Fibers in Scars. Issue 5 (September 2017) - Xie, Hua; Lucchesi, Lisa; Zheng, Bo; Ladich, Elena; Pineda, Teresa; Merten, Rose; Gregory, Cynthia; Rutten, Michael; Gregory, Kenton
Abstract : Tropoelastin (TE), the soluble precursor of insoluble elastin fibers, is produced in minimal amounts in adults. Burn injuries result in inflexible collagen-rich scars because of lack of elastin fiber formation. We studied the feasibility of using recombinant human tropoelastin to enable elastin fiber production in burn and surgical scars to improve skin flexibility. In a swine hypertrophic burn scar model, normal skin and 3 × 3-cm 2 partial thickness thermal burns underwent dermatome resection at 1 week post burn and randomized to four subcutaneous injections of saline or TE (either 0.5, 5, or 10 mg/ml) spaced 3 days apart. Two burn sites received TE injections after wound closure (0.5 or 10 mg/ml). At 90 days, skin hardness, flexibility, and histology were evaluated. All injury sites developed hypertrophic scars. New elastin fibers were found in burn scars in all injuries injected after skin closure with low (5/5) and high (6/6) TE doses ( P < .05). No elastin fibers were observed without TE treatment. No significant differences in skin hardness, flexibility, or inflammation were observed. This is the first report demonstrating that subcutaneous injections of TE into surgical and burn injuries can safely produce new elastin fibers in scars. Despite the development of new elastin fibers, skin flexibility was not improved, possibly because of insufficient elastin fiber maturation or the hypertrophic model used. The ability to restore elastin fiber formation in adult skin after burns, trauma, and surgery may improve skin regeneration and reduce disabling complications of scar formation.